Valuation of Lithium Mining Waste for Water Treatment: An Experimental Study and Broader Implications of Residual Aluminum Silicate (Al2SiO5) as an Artificial Zeolite (International Journal of Geoscience, Engineering and Technology, 2025)
This study explored the potential of residual aluminum silicate (Al2SiO5), a mining byproduct collected from Brazilian Lithium Company (CBL), as a flocculating agent in the treatment of clay particle-laden waters. The experiments evaluated the material's ability to aggregate particles and reduce water turbidity under different conditions, acting as an artificial zeolite. Results demonstrated the effectiveness of residual aluminum silicate in flocculation, outperforming the control treatment. It was observed that the flocculant's performance was influenced by the medium's pH, being more efficient under alkaline conditions. This work suggests that residual aluminum silicate is a promising candidate for water treatment, but highlights the need for further understanding of its action and optimization for large-scale applications.
Keywords: Aluminum silicate; Waste; Water treatment; Artificial zeolite; Turbidity